When pulmonary embolism mimics pneumonia: An interesting case report - C S Sooraj; Vasantha Kamath; Shreyashi Ganguly (Wolters Kluwer Medknow Publications, 2021)
The classic presentation of pulmonary embolism is rather uncommon. The lack of pathognomonic signs and symptoms makes the diagnosis of PE difficult. Here, we report a patient presented with symptoms suggestive of pneumonia and ultimately diagnosed as PE. A 75 years old male patient with no known co-morbidity, presented with of breathlessness for 1 week, cough for one week, productive in type, with scanty sputum, chest pain since one week, sharp, aggravated on coughing. His respiratory system examination revealed increased VF/VR in right mammary and left infrascapular areas, equal air entry with normal vesicular breath sounds, crepitations in the right mammary and left infrascapular areas. He was initially treated as pneumonia but did not respond. His chest X-ray PA view showed probable mass lesion in the right para cardiac region, ECG- sinus tachycardia with right axis deviation and RV strain pattern. CECT Thorax- Intraluminal thrombus in Rt and Lt pulmonary artery consistent with acute pulmonary thromboembolism.The patient was lysed with Inj. Streptokinase and subsequently improved over the next 6 days. Whilst established criteria aid in ruling in or out the diagnosis in a setting, the gestalt of a clinician is the most appropriate defence against a missed diagnosis especially in settings of confounded presentation. Therefore, until conclusively proven with the help of imaging and lab-work, PE should be a diagnosis that needs be considered in any case of atypical pneumonia who is not responding to first line therapies.